A randomized controlled trial of a self‐management psychosocial intervention for men with prostate cancer and their partners: a study protocol. (25th March 2013) - McCaughan, Eilis; Prue, Gillian; McSorley, Oonagh; Northouse, Laurel; Schafenacker, Ann; Parahoo, Kader
Abstract Background Little is known about interventions to help men and their partners cope with the after effects of prostate cancer treatment. The lack of in‐depth descriptions of the intervention content is hindering the identification of which intervention (or component of an intervention) works. Aim To describe the development and evaluation of the content of a self‐management psychosocial intervention for men with prostate cancer and their partners. Design A feasibility randomized controlled trial including structure, process, and outcome analysis. Methods This 9‐week intervention commences on completion of treatment and consists of three group and two telephone sessions. The intervention focuses on symptom management, sexual dysfunction, uncertainty management, positive thinking and couple communication. Forty‐eight couples will be assigned to either the intervention or a control group receiving usual care. Participants will be assessed at baseline, immediately postintervention and at 1 and 6 months postintervention. Outcome measures for patients and caregivers include self‐efficacy, quality of life, symptom distress, uncertainty, benefits of illness, health behaviour, and measures of couple communication and support. An additional caregiver assessment will be completed by the partner. Discussion The main purpose of this feasibility study is to investigate the acceptability of the CONNECT programme to men with prostate cancer and their partners and to gain feedback from the participants and facilitators to make changes to and enhance the programme. Reasons why men do not want to participate will be collated to enhance recruitment in the future. We will also test recruitment strategies, randomization procedures, and the acceptability of the questionnaires. Ethical approval granted December 2010.